Varying degrees of homostructurality in a series of cocrystals of antimalarial drug 11‐azaartemisinin with salicylic acids. Issue 6 (6th May 2021) - Roy, Monalisa; Li, Keyao; Nisar, Madiha; Wong, Lawrence W.-Y.; Sung, Herman H.-Y.; Haynes, Richard K.; Williams, Ian D.
Abstract : Cocrystals of the antimalarial drug 11‐azaartemisinin (11‐Aza) with salicylic acid (SalA) were reported recently and showed an enhanced dissolution rate. The use of bromo‐substituted SalA compounds has now allowed the isolation of a larger family of these 1:1 cocrystals. All the structures involve molecular pairs with (8) heterosynthons between the 11‐Aza lactam functionality and the benzoic acid group that are organized into highly preserved 21 stacks. These are organized into either isostructural (5‐BrSalA) or modified arrangements (4‐BrSalA and 3, 5‐Br2 SalA), with varying degrees of homostructurality compared to the parent SalA cocrystal. Abstract : The X‐ray structures of three new 1:1 pharmaceutical cocrystals of 11‐azaartemisinin (11‐Aza; systematic name: 1, 5, 9‐trimethyl‐14, 15, 16‐trioxa‐11‐azatetracyclo[10.3.1.0 4, 13 .0 8, 13 ]hexadecan‐10‐one, C15 H23 NO4 ) with bromo‐substituted salicylic acids [namely, 5‐bromo‐ (5‐BrSalA, C7 H5 BrO3 ), 4‐bromo‐ (4‐BrSalA, C7 H5 BrO3 ) and 3, 5‐dibromosalicylic acid (3, 5‐Br2 SalA, C7 H4 Br2 O3 )] are reported. All the structures are related to the parent 11‐Aza:SalA cocrystal (monoclinic P 21 ) reported previously. The 5‐BrSalA analogue is isostructural with the parent, with lattice expansion along the c axis. The 4‐BrSalA and 3, 5‐Br2 SalA cocrystals retain the highly preserved 21 stacks of the molecular pairs, but these pack with a varying degree of slippage with respect to neighbouring stacks, altering the close contacts between them, and represent two potential alternative homostructural arrangements for the parent compound. Structure redeterminations of the bromosalicylic acids 5‐BrSalA, 4‐BrSalA and 3, 5‐Br2 SalA at 100 K show that the packing efficiency of the cocrystals need not be higher than the parent coformers, based on specific‐volume calculations, attributable to the strong O—H…O=C hydrogen bonds of 2.54 Å in the cocrystals.